Continued Fractions and Unique Factorization on Digraphs - Giscard, P; Thwaite, S; Jaksch, D (2012)
We show that the characteristic series of walks (paths) between any two vertices of any finite digraph or weighted digraph G is given by a universal continued fraction of finite depth involving the simple paths and simple cycles of G. A simple path is a walk forbidden to visit any vertex more than once. We obtain an explicit formula giving this continued fraction. Our results are based on an equivalent to the fundamental theorem of arithmetic: we demonstrate that arbitrary walks on G uniquely factorize into nesting products of simple paths and simple cycles. Nesting is a walk product which we define. We show that the simple paths and simple cycles are the prime elements of the ensemble of all walks on G equipped with the nesting product. We give an algorithm producing the prime factorization of individual walks. We obtain a recursive formula producing the prime factorization of ensembles of walks. Our results have already found applications in the field of matrix computations. We give examples illustrating our results.